A Novel Molecularly Imprinted Photoelectrochemical Sensor Based on g‐C3N4‐AuNPs for the Highly Sensitive and Selective Detection of Triclosan. Issue 2 (18th December 2017) - Feng, Shasha; Wei, Xiaoping; Zhong, Li; Li, Jianping
Abstract: A novel molecularly imprinted polymer (MIP) photoelectrochemical sensor was fabricated for the highly sensitive and selective detection of triclosan. The MIP photoelectrochemical sensor was fabricated using graphite‐like carbon nitride (g‐C3 N4 ) and gold nanoparticles (AuNPs) as photoelectric materials. The MIP/g‐C3 N4 ‐AuNPs sensor used photocurrent as the detection signal and was triggered by ultraviolet light (UV‐Light 365 nm). g‐C3 N4 ‐AuNPs was immobilized on indium tin oxide electrodes to produce the photoelectrochemically responsive electrode of the MIP/g‐C3 N4 ‐AuNPs sensor. A MIP layer of poly‐ o ‐phenylenediamine was electropolymerized on the g‐C3 N4 ‐AuNPs‐modified electrode to act as the recognition element of the MIP/g‐C3 N4 ‐AuNPs sensor and to enable the selective adsorption of triclosan to the sensor through specific binding. Under optimal experimental conditions, the designed MIP/g‐C3 N4 ‐AuNPs sensor presented high sensitivity for triclosan with a linear range of 2×10 −12 to 8×10 −10 M and a limit of detection of 6.01×10 −13  M. Moreover, the MIP/g‐C3 N4 ‐AuNPs sensor showed excellent selectivity. The sensor had been successfully applied in the analysis of toothpaste samples. Abstract :